FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT KAJANG KABUPATEN BULUKUMBA - Akhmad Akhmad (AkMen JURNAL ILMIAH, 2013)
This study uses the variable motivation, ability, discipline, leadership and communication as variables that influence employee performance. Results of multiple regression statistic value to test the hypothesis statistical values ​​obtained results 0,042 work motivation, work ability 0.000, 0.006 work discipline, leadership 0.001, 0.002 and communications, these results indicate that statistically significant then the hypothesis is accepted. Statistically explained that the factors affecting the performance of the first employees work motivation has a significant influence on employee performance, both kemempuan work have a significant influence on employee performance, the third discipline has an influence on employee performance, the four leadership has an influence on the performance of employees, and the fifth communication have an influence on employee performance. The findings for the factors that affect the performance indicates that motivation, increased employability, leadership and employee communications will improve the performance of employees at Head Office Bulukumba Kajang